Hubungan Sumber Informasi dan Sikap Ibu Terhadap Kelengkapan Imunisasi Dasar pada Balita di Wilayah Kerja Puskesmas Pulau Kupang Kuala Kapuas - Nurul Hidayah; Desilestia Dwi Salmarini; Sakiah (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Immunization is an effort to actively reduce the number of illnesses, deaths and disabilities due to diseases that can be prevented by immunization (PD3I). The role of parents, especially mothers, in the immunization program is very important. Therefore, sources of information and attitudes influence mothers' awareness of taking their toddlers for immunization. To determine the relationship between sources of information and mothers' attitudes towards the completeness of basic immunization for toddlers in the Kupang Island Community Health Center working area. Quantitative research uses a cross sectional approach. The research population was toddlers aged 12 - 24 months using Purposive Sampling technique, totaling 45 respondents. The measuring instrument used was a questionnaire whose results were analyzed using the Fisher Exact test. Respondents with sufficient sources of information and complete immunization were 15 (33.3%) toddlers. The Fisher Exact test results show a p value of 0.019. Meanwhile, 24 (53.4%) toddlers had complete immunization and 2 (4.4%) toddlers had incomplete immunization. The Fisher Exact test results show a p value of 0.010. The source of information and the mother's attitude have an influence on the completeness of basic immunization for toddlers in the Kupang Island Kuala Kapuas Health Center working area.